The southernmost occurrence of Brachycarcharias (Lamniformes, Odontaspididae) from the Eocene of Antarctica provides new information about the paleobiogeography and paleobiology of Paleogene sand tiger sharks - Giuseppe Marramà (Department of Palaeontology, Faculty of Earth Sciences, Geography and Astronomy, University of Vienna); Andrea Engelbrecht (Department of Palaeontology, Faculty of Earth Sciences, Geography and Astronomy, University of Vienna); Thomas Mörs (Department of Paleozoology, Swedish Museum of Natural History); Marcelo A. Reguero (Division Paleontologia de Vertebrados, Museo de La Plata); Jürgen Kriwet (Department of Palaeontology, Faculty of Earth Sciences, Geography and Astronomy, University of Vienna) (Università degli Studi di Milano (University of Milan), 2018)
The abstract is available here: https://uscholar.univie.ac.at/o:1073127 The abstract is available here: https://uscholar.univie.ac.at/o:1073127